How Lifestyle and Quality Drive Chatime Purchases in Indonesia: Bagaimana Gaya Hidup dan Kualitas Mendorong Pembelian Chatime di Indonesia - Saptarianto, Bayu Alief; Oetarjo, Mas (Indonesian Journal of Law and Economics Review, 2024)
Technological developments have significantly impacted the lifestyle of Indonesian people. This research investigates how taste, product quality, and lifestyle influence purchasing decisions for Chatime products at Lippo Plaza Sidoarjo Mall. Using a quantitative method with Simple Random Sampling, data from 100 respondents were collected via Likert scale questionnaires and analyzed using linear regression. The results show that taste, product quality, and lifestyle positively and significantly affect purchasing decisions. These findings highlight the importance of improving product attributes and aligning marketing strategies with consumer lifestyles to enhance purchasing decisions. Future studies should explore broader demographics and diverse data collection methods. Highlight: Taste, product quality, and lifestyle positively influence purchasing decisions. Quantitative method with Simple Random Sampling used for data collection. Linear regression analysis confirms significant effects on purchasing behavior. Keywoard: Technological impact, Lifestyle, Purchasing decisions, Chatime, Linear regression